Isolation and Characterization of Endofytic Bacteria Indigenus Potentially Producing IAA (Indole Acetic Acid) in West Sumatera and Their Effect on Nursery Palm Oil (Elaeis guineensis jacq) - Rover Rover; Reni Mayerni; Yulmira Yanti; Auzar Syarif (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2019)
The IAA potentials of endophytic bacteria indigenous isolated from roots palm oil in west Sumatra. Isolate were characterized on the basis of visual observation, gram staining, hypersensitive reaction and IAA producing bacteria. Subsequently, effect on plant growth was tested by nursery palm oil used random design block. Out of 82 isolates, base on gram test 12 isolates were gram negative and 70 isolates grams positive and then results on the reaction hypersensitive test (HR test) there are 8 isolates that positive which means the isolate cannot be applied on the soil and plant. Eighty isolates selected were able to produce IAA that was between ppm 0,30ppm - 3,65ppm. Seven isolates showed clearly the growth promoting plant under field condition. Hence, these isolates are promising plant growth promoting isolates showing multiple attributes that can significantly influence the nursery palm oil. The result of present study, treatment E3.1.2 has higher plant most of the other treatment i.e. 21,93 cm and number of leaves i.e. 4,33 leaves.